2014
DOI: 10.1063/1.4899263
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the high resolution infrared spectrum of methane (12CH4 and 13CH4): Partial vibrational assignment extended towards 12 000 cm−1

Abstract: We have recorded the complete infrared spectrum of methane (12)CH4 and its second most abundant isotopomer (13)CH4 extending from the fundamental range starting at 1000 cm(-1) up to the overtone region near 12,000 cm(-1) in the near infrared at the limit towards the visible range, at temperatures of about 80 K and also at 298 K with Doppler limited resolution in the gas phase by means of interferometric Fourier transform spectroscopy using the Bruker IFS 125 HR prototype (ZP 2001) of the ETH Zürich laboratory.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 131 publications
0
38
0
2
Order By: Relevance
“…A recent contribution by Ulenikov et al [21] is of particular relevance for our work. These authors reported the FTS high resolution spectrum of methane from 1000 to 12,000 cm À 1 at 80 K and 298 K. A multireflection collisional cooling cell with absorption path length between 5 and 15 m was used for the low temperature recordings.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 97%
See 3 more Smart Citations
“…A recent contribution by Ulenikov et al [21] is of particular relevance for our work. These authors reported the FTS high resolution spectrum of methane from 1000 to 12,000 cm À 1 at 80 K and 298 K. A multireflection collisional cooling cell with absorption path length between 5 and 15 m was used for the low temperature recordings.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 97%
“…Unfortunately no line list was constructed and only the P(1) line center values were provided by the authors (Table IV of Ref. [21]). We present in Fig.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Further important questions can be addressed by the study of molecules important for the spectroscopy of the Earth's atmosphere [16][17][18][19][20][21][22][23][24]. In the past, much high resolution spectroscopic work has concentrated on relatively simple atmospheric trace gases such as ozone [18], methane [20][21][22][23][24] or some of the simpler fluoro-chloro-hydrocarbons [25], to name just a few selected examples from a very large body of work usually based on FTIR spectroscopy with conventional light sources.…”
Section: Introductionmentioning
confidence: 99%